Let's play! : poems about sports and games from around the world - Adl, Shirin; Chatterjee, Debjani; D'Arcy, Brian G. (Brian Gerard) (Frances Lincoln Children's Books, 2013)
Collects thirty-seven poems celebrating such sports and games as football, baseball, judo, table tennis, netball, cycling, chess, and scrabble.